Analisis Struktur Modal Terhadap WACC dan Analisis WACC Terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Rokok Yang Terdaftar di BEI Periode 2009-2013) - Hari Sulistiyo (UNSIKA (Universitas Singaperbangsa Karawang), 2017)
Cost of capital is very important for a company in their business especially to analyze cost of capital to the rate of investment’s return. The higher the investor’s demands for the share, the higher the share’s price. The objective of this study is to examine empirically if capital structure has a positive effect to the firm’s value and if cost of capital has a negative effect to the firm’s value. Capital structure is represented by long-term debt to equity ratio, cost of capital is represented by weighted-average cost of capital (WACC), and firm’s value is represented by average stock price. Samples used in this research are 3 manufacture companies which are listed in Indonesian Stock Exchange period 2009-2013. Analytical method which is used to test the influence of capital structure and Cost of Capital (in this case, WACC) against value of companies is simple regression analysis. The result of this research shows that capital structure has positive effect to the firm’s value. That shows if higher the value of capital structure it will make the higher firm’s value. Besides that, this research also shows that cost of capital has no negative effect to the firm’s value. It’s caused by global crisis in 2008 that makes liability and stock price unstable.